2020
DOI: 10.1111/jcmm.15429
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics analysis of the biological changes involved in the osteogenic differentiation of human mesenchymal stem cells

Abstract: The mechanisms underlying the osteogenic differentiation of human bone marrow mesenchymal stem cells (hBMSCs) remain unclear. In the present study, we aimed to identify the key biological processes during osteogenic differentiation. To this end, we downloaded three microarray data sets from the Gene Expression Omnibus (GEO) database: GSE12266, GSE18043 and GSE37558. Differentially expressed genes (DEGs) were screened using the limma package, and enrichment analysis was performed. Protein‐protein interaction ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 60 publications
0
18
0
Order By: Relevance
“…hMSCs are self-renewing precursor cells that can differentiate into bone, fat, cartilage, and stromal cells of the bone marrow ( Frenette et al, 2013 ). It has been reported that they are ideal seed cells for bone tissue engineering ( Fan et al, 2020 ). Notably, however, the effective cultivation of BMSCs requires a good culture environment and a good in vitro culture technique.…”
Section: Discussionmentioning
confidence: 99%
“…hMSCs are self-renewing precursor cells that can differentiate into bone, fat, cartilage, and stromal cells of the bone marrow ( Frenette et al, 2013 ). It has been reported that they are ideal seed cells for bone tissue engineering ( Fan et al, 2020 ). Notably, however, the effective cultivation of BMSCs requires a good culture environment and a good in vitro culture technique.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, through the DEGs analysis of multiple datasets, the gene changes of PDLSCs after osteoinduction were obtained, and the GO enrichment analysis of DEGs was performed. Fan reported ( Fan et al, 2020 ) that the main enrichment pathways of BMSCs osteogenic differentiation were extracellular matrix organization, ossification, negative regulation of cell proliferation, vasculature development, cell division and spindle. Wang reported ( Yang et al, 2019 ) that regulation of the cellular amino acid metabolic process, DNA metabolic process and regulation of apoptotic process were mostly enriched during the osteogenic differentiation of BMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Microarray techniques and bioinformatics analysis have been widely used to screen for the DEGs, functional pathways and PPI associated with osteogenic differentiation of stem cells ( Yang et al, 2019 ; Fan et al, 2020 ; Bini et al, 2021 ; Shin et al, 2021 ). In this study, three microarray datasets (total 16 samples) were downloaded from Gene Expression Omnibus (GEO) for analysis to identify DEGs and DEMs between the control group and the induction group.…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the DE genes in PAITA. The limma package (http://bioconductor.org/packages/limma/) (23) in r software (version 3.2.11, http://www.bioconductor. org/packages/release/bioc/html/clusterProfiler.html) (24) was used to perform data preprocessing, including background correction, quantile normalization and probe summarization, to obtain the probe expression matrix (25).…”
Section: Methodsmentioning
confidence: 99%
“…The limma package ( ) ( 23 ) in R software (version 3.2.11, ) ( 24 ) was used to perform data preprocessing, including background correction, quantile normalization and probe summarization, to obtain the probe expression matrix ( 25 ). UCSC RefSeq database ( ), miRBase database 21 ( ) and NONCODE V4 database ( ) were used to perform the blast comparison (identity >95%, coverage >95) and obtain the gene ID ( 26 ).…”
Section: Methodsmentioning
confidence: 99%